The Performance of Dow Jones Country Islamic Indexes Against Dow Jones Country Conventional Indexes in Asia and the Middle East : An Empirical Study of the Last Decade - Suharwardy, Zain (2013)
This paper attempts to examine the performance of six countries spanning from Asia and the Middle East. Countries are selected from the Dow Jones Islamic Market Index and the focus is kept to only choose countries that have an active Dow Jones Islamic Market Country Index along with a parallel Dow Jones Conventional Country Index. Further break down is made by comparing the country performances to their respective Dow Jones regional index’s (Dow Jones Asia Index and the Dow Jones MENA) in order to determine whether the country has performed better or worse than its specific region. Comparisons are made between the Dow Jones Islamic and Conventional Indexes in order to examine their risk return characteristics and take into consideration whether Islamic indexes are more volatile or less volatile than their conventional indexes. The Sharpe ratio, Treynor ratio and Jensen alpha are used to measure the risk return volatility of the indexes. Correlation tests are also run to compare the Islamic and Non Islamic indexes to each other. The data sample period is from October 2002 till June 2012 (3551 data entries) and the daily closing prices of the indices are used. This data is further broken down into two sub-periods: October 2002 to December 2006 (1553 data entries) and January 2007 to June 2012 (1998 data entries). However for certain countries like Dow Jones Dubai Index (started 31 December 2003), Dow Jones Turkey Index and Dow Jones Islamic Market Turkey Index (started 1st January 2003), Dow Jones China Islamic Index (started 20th Dec 2005), Dow Jones Pakistan Index (started 30th December 2005) and Dow Jones Islamic Pakistan Index (started 30th June 2004) the daily closing prices have been recorded since their start till June 2012.